4(x-4)=(x-26)

Simple and best practice solution for 4(x-4)=(x-26) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-4)=(x-26) equation:


Simplifying
4(x + -4) = (x + -26)

Reorder the terms:
4(-4 + x) = (x + -26)
(-4 * 4 + x * 4) = (x + -26)
(-16 + 4x) = (x + -26)

Reorder the terms:
-16 + 4x = (-26 + x)

Remove parenthesis around (-26 + x)
-16 + 4x = -26 + x

Solving
-16 + 4x = -26 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-16 + 4x + -1x = -26 + x + -1x

Combine like terms: 4x + -1x = 3x
-16 + 3x = -26 + x + -1x

Combine like terms: x + -1x = 0
-16 + 3x = -26 + 0
-16 + 3x = -26

Add '16' to each side of the equation.
-16 + 16 + 3x = -26 + 16

Combine like terms: -16 + 16 = 0
0 + 3x = -26 + 16
3x = -26 + 16

Combine like terms: -26 + 16 = -10
3x = -10

Divide each side by '3'.
x = -3.333333333

Simplifying
x = -3.333333333

See similar equations:

| 6x/8=-18 | | 5(x+6)=4x+3 | | -5=26w | | -7u=-22 | | 57=-y/4 | | 2/(3-2x)=1 | | x=y^2+7y+c | | 0=-x^2-6x-3 | | 8=x+(x+92) | | I=P(r+nt) | | 5x+2x=1260 | | 5(x+2)+12=-24 | | 5x-3/9 | | 3x-7+9-2x=28 | | (3+i)z^2+(5-5i)z+(-2+16i)=0 | | 2/3x-25=-29 | | 4x+3y=2x-6y | | (1+x^2)dy=(1+xy)dx | | 7y-12=4y+2 | | X^2+100x-15000=0 | | 9z-6-5z=-14 | | 0.7x-0.6(50+x)=-0.44(50) | | 15sinx+8cosx=this(x-a) | | 5b+20=10b | | 25-6x=-29 | | 9(m-4)-8(m+2)=-52 | | 3a+4b=70 | | 7-(4z-1)=2-5z | | 3a+4b=35 | | (2k+1)(xsquare+1)=(2k+5)x | | a-21/x=4 | | x-21/x=4 |

Equations solver categories